Disparities in social assistance receipt between immigrants and natives in Sweden - Björn Gustafsson (Institute for the Study of Labor (IZA), 2011)
Social assistance receipt among immigrants in relation to receipt among natives in Sweden is investigated. A background of how the system is constructed is provided, statistical information reported, the literature surveyed and key results interpreted. Most out-payment for social assistance in Sweden refers to foreign born persons although the category makes up 14 percent of the population. While some part of the high costs can be attributed to needs to maintaining recent refugees, this is not the entire story. Immigrants tend to assimilate out of social assistance receipt. However, receipt continues to be higher than among in several characteristics identical natives many years after immigration among immigrants from not rich countries. The elevated probabilities of social assistance receipt among immigrants from not rich countries are mainly due to failures of integrating into the labor market at the destination.
urn:nbn:de:101:1-201112136771
Keywords: F22; I38; J15; 330; social assistance; immigrants; Sweden; Migranten; Sozialhilfeempfänger; Vergleich; Bevölkerung; Schweden